Plastic Changes in the Spinal Cord in Motor Neuron Disease. (16th April 2014) - Fornai, Francesco; Ferrucci, Michela; Lenzi, Paola; Falleni, Alessandra; Biagioni, Francesca; Flaibani, Marina; Siciliano, Gabriele; Giannessi, Francesco; Paparelli, Antonio
Abstract : In the present paper, we analyze the cell number within lamina X at the end stage of disease in a G93A mouse model of ALS; the effects induced by lithium; the stem-cell like phenotype of lamina X cells during ALS; the differentiation of these cells towards either a glial or neuronal phenotype. In summary we found that G93A mouse model of ALS produces an increase in lamina X cells which is further augmented by lithium administration. In the absence of lithium these nestin positive stem-like cells preferentially differentiate into glia (GFAP positive), while in the presence of lithium these cells differentiate towards a neuron-like phenotype ( β III-tubulin, NeuN, and calbindin-D28K positive). These effects of lithium are observed concomitantly with attenuation in disease progression and are reminiscent of neurogenetic effects induced by lithium in the subependymal ventricular zone of the hippocampus.